Technical Evaluation of Android Parental Control Tools and PDNS Filtering Services: The Chilean Context - Rojas, Nicolas; Boettcher, Nicolas; Jativa, Pablo Palacios; Sanchez, Ivan (IEEE access, 2025)
The growing exposure of Children and Adolescents (C&A) to online risks has led to the widespread adoption of parental control tools. However, in Chile, the legal framework that requires ISPs to offer such solutions does not establish minimum standards for the functionality or effectiveness of these solutions. This study presents a comprehensive technical and functional evaluation of mobile applications and Protective DNS (PDNS) filtering services available within the Chilean context. The most downloaded Android applications claiming to have parental control capabilities were selected. They were evaluated through practical tests on 1,427 categorized websites, on various versions of Android, including rooted and non-rooted devices. Assessing the detection of rooted devices, evasion resistance, among others. The evaluation considered ten key parental control functionalities, URL and IP filter accuracy, resistance to evasion techniques, and a novel Functionality Index (FI), designed to enable standardized and objective comparison of tools. The results reveal significant disparities: Although tools such as Google Family Link and Kaspersky demonstrate strong performance even under adverse conditions, others, despite their popularity or endorsement by Chilean ISPs, fail to provide basic protections. For the same set of websites, access to them was verified through PDNS services that had filters for adult and gambling categories. The results obtained show inconsistent accuracy, with high rates of false positives in legitimate categories and low effectiveness in filtering adult content. These findings highlight the need for standardized evaluation mechanisms and greater oversight to ensure effective digital protection for C&A.